Prevention of Mental Health Disorders Using Internet- and Mobile-Based Interventions: A Narrative Review and Recommendations for Future Research - Ebert, David Daniel; Cuijpers, Pim; Muñoz, Ricardo F.; Baumeister, Harald (Frontiers in Psychiatry, 2017)
Although psychological interventions might have a tremendous potential for the prevention of mental health disorders (MHD), their current impact on the reduction of disease burden is questionable. Limitations of traditional prevention programs could potentially be overcome by providing Internet- and mobile-based interventions (IMIs). This article provides an introduction to the subject, discusses areas of application, and narratively reviews the available evidence for the efficacy and cost-effectiveness of IMIs with regard to the prevention of MHD onset. Subsequently we provide recommendations for future research. We identified ten randomized trials of which six found significant effects in favor of the intervention group. With regard to specific disorders, only for the indicated prevention of depression is there consistent evidence (across 4 trials). The only trial on the prevention of general anxiety did not result in positive findings. With regard to the prevention of eating disorders, positive effects were only found in post-hoc subgroup analyses, indicating that it might be possible to prevent eating disorder onset for specific subpopulations of people at risk of developing eating disorders. Only one study evaluated the cost-effectiveness of an IMI and found that an indicated intervention for the prevention of depression had a high likelihood for providing good value for the money spent. Disorders not examined so far include for example substance use, psychotic-, bipolar-, stress-related-, phobic- and panic-, obsessive-compulsive-, impulse-control-, somatic symptom disorder and insomnia. No published study so far has evaluated the effect of a mobile only preventive intervention on disorder onset or made use of phone- or wearable sensors. In summary, available evidence clearly indicates the huge potential of IMIs for the prevention of MHD.However, there is a need for more rigorously conducted large scale randomized controlled trials. Future directions for the field are discussed that seem necessary in order to fully exploit the potential of IMI for the prevention of MHD. Among others these are the need to evaluate m-health interventions, the cost-effectiveness of IMIs; interventions in children and adolescents; the role of human support in preventive interventions; possible adverse effects of MHD prevention IMIs; and strategies to increase utilization of available interventions.